Tbet and IL-36γ cooperate in therapeutic DC-mediated promotion of ectopic lymphoid organogenesis in the tumor microenvironment. (3rd June 2017) - Weinstein, Aliyah M.; Chen, Lu; Brzana, Emily A.; Patil, Prashanti R.; Taylor, Jennifer L.; Fabian, Kellsye L.; Wallace, Callen T.; Jones, Sabrina D.; Watkins, Simon C.; Lu, Binfeng; Stroncek, David F.; Denning, Timothy L.; et al.
ABSTRACT: We have previously reported that direct injection of dendritic cells (DC) engineered to express the Type-1 transactivator Tbet (i.e., DC.Tbet) into murine tumors results in antitumor efficacy in association with the development of structures resembling tertiary lymphoid organs (TLO) in the tumor microenvironment (TME). These TLO contained robust infiltrates of B cells, DC, NK cells, and T cells in proximity to PNAd + blood vessels; however, they were considered incomplete, since the recruited B cells failed to organize into classic germinal center-like structures. We now report that antitumor efficacy and TLO-inducing capacity of DC.Tbet-based i.t. therapy is operational in peripheral lymph node-deficient LTA −/− mice, and that it is highly dependent upon a direct Tbet target gene product, IL-36γ/IL-1F9. Intratumoral DC.Tbet fails to provide protection to tumor-bearing IL-36R −/− hosts, or to tumor-bearing wild-type recipient mice co-administered rmIL-1F5/IL-36RN, a natural IL-36R antagonist. Remarkably, the injection of tumors with DC engineered to secrete a bioactive form of mIL-36γ (DC.IL36γ) also initiated therapeutic TLO and slowed tumor progression in vivo . Furthermore, DC.IL36γ cells strongly upregulated their expression of Tbet, suggesting that Tbet and IL-36γ cooperate to reinforce each other's expression in DC, rendering them competent to promote TLO formation in an "immunologically normalized, " therapeutic TME.